The unbreakable code - Bertman, Jennifer Chambliss (Bertman, Jennifer Chambliss. Book Scavenger, 2018)
Emily and James discover a series of encrypted messages in Mark Twain books hidden via Book Scavenger, and each hidden book they find seems to trigger an act of arson. The sleuthing friends dig deeper and start to suspect Mr. Quisling as the arsonist, hiding his tracks as he hunts for the legendary unbreakable code.